Legal Protection for Victims of Domestic Violence in Islamic Law-Based Countries: A Comparative Review - Anwar, Saeful (Journal of Islamic Family Law, 2025)
Domestic violence (DV) is a serious social issue that impacts the health and well being of victims. In Islamic law based countries, legal protection for DV victims is often impeded by social stigma, cultural norms, and legal challenges. This study aims to analyze the legal protection available for DV victims in Indonesia, Malaysia, and Saudi Arabia, as well as to explore the effectiveness of the approaches adopted by each country. A qualitative approach was employed, utilizing in-depth interviews and analyzing relevant secondary data. Respondents included DV victims, NGO activists, and legal practitioners. The findings indicate that, while each country has a legal framework in place to protect victims, the application and effectiveness of these frameworks vary significantly. In Indonesia, a preventive approach is hindered by limited law enforcement. In Malaysia, although strict penalties are available, stigma prevents victims from reporting incidents. Meanwhile, in Saudi Arabia, despite legal reforms, cultural interpretations often confuse victims regarding their rights. This conclusion highlights the need for legal reforms that are more sensitive to cultural contexts and for increased collaboration between the government and civil society organizations to enhance effective protection for DV victims.